Placebo response to caffeine improves reaction time performance in sleepy people - Anderson, Clare; Horne, James A. (Human psychopharmacology, 2008)
Caffeine is the most widely used stimulant to counteract sleepiness. However, little is known about any placebo effect of caffeine in sleepy people and the effect of suggestibility. Over a 95 min test period, and in a counterbalanced design, 16 young healthy adults underwent 3 × 30 min sessions at the psychomotor vigilance test (PVT), during an early afternoon ‘dip’ enhanced by a prior night's sleep restriction (5 h). On both occasions they were given a cup of a decaffeinated coffee; once when the participant was verbally primed to suggest the coffee was caffeinated (Placebo) and on the other under neutral priming (Control). There were significantly fewer lapses and shorter reaction times following Placebo, for the initial two 30 min sessions, indicating that suggestion about consuming caffeine was effective in improving performance in moderately sleepy people. Copyright © 2008 John Wiley & Sons, Ltd.